Evolución del sistema financiero peruano y su reputación bajo el índice Merco. Período: 2010-2014 - Lizarzaburu Bolaños, Edmundo R. (2016)
The aim of this study is to analyse the evolution and performance of the Peruvian financial system in the last few years, as well as the role of the banking reputation in this, taking different bases such as the Merco Index and financial solvency. The study is both quantitative and qualitative, and is specifically focused on the 4 most representative banks of the system, and selected on the basis of investments, deposits, and assets. The analysis looks to establish an initial relationship between corporative reputation (through the value of the Merco Index) and financial solvency, with the analysis being able to be complemented with further studies with the other indicators that are shown in Annexes 1 to 3.